A novel optical chemical sensor for the determination of nickel(II) based on fluorescence quenching of newly synthesized thiazolo-triazol derivative and application to real samples - Aksuner, Nur; Henden, Emur; Yilmaz, Ibrahim; Cukurovali, Alaaddin (Elsevier Science Sa, 2012)
The characterization of a new optical sensor membrane is described for the determination of Ni(II) based on the immobilization of the fluorescent thiazolo-triazol derivative in PVC matrix. This optode has a wide linear range of 1.0 x 10(-9)-4.4 x 10(-3) Mat pH 6.0 for Ni(II) ions with the detection limit of 8.5 x 10(-10) M. The response of the optode membrane to Ni(II) is fully reversible and reveals a very good selectivity towards Ni(II) ion over a wide variety of other metal ions in solution. The membrane showed a good durability and short response time with no evidence of reagent leaching. The proposed optical sensor gives good results for applications in direct determination of Ni(II) in real samples that are satisfactorily comparable with corresponding data from flame atomic absorption spectrometry. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Thiazolo-triazol; PVC matrix; Optical sensor; Fluorescence spectroscopy; Nickel(II)